Enseigner l’analyse du discours en langue étrangère. En quoi consiste le cours de spécialisation en linguistique destiné aux étudiants du 2nd cycle ? - Pirogowska, Ewa (Studia Romanica Posnaniensia, 2017)
The paper addresses the two following questions: 1) how should a discourse perspective on specialized communication training course be introduced ? 2) should student’s identity attending a course in specialized communication be taken into account, or, conversely, left out ? Special attention is paid to methodological problems of teaching linguistics. Two MA postgraduate programmes run at Romance Philology are taken as examples La manipulation et ses aspects linguistiques (Linguistic aspects of interpersonal manipulation) and L’image linguistique du monde. Les stéréotypes racistes dans la langue et la culture (Racist stereotypes in language and culture).